Bacterial growth and ceftriaxone activity in individual ascitic fluids in an in vitro model of spontaneous bacterial peritonitis - Wisse van Os; Beatrix Wulkersdorfer; Sabine Eberl; Zoe Oesterreicher; Philipp Schwabl; Thomas Reiberger; Rafael Paternostro; Maria Weber; Birgit Willinger; Markus Zeitlinger (Frontiers Media S.A., 2023)
Introduction: The environment of the infection site affects bacterial growth and antibiotic activity. When bacterial growth and antibiotic activity are studied in body fluids, samples of multiple subjects are usually pooled, averaging out potentially relevant differences in composition. The ascitic fluid (AF) environment is frequently associated with spontaneous bacterial peritonitis (SBP) in cirrhotic patients. In this study, bacterial growth and ceftriaxone activity were evaluated in individual AF using an in vitro model of SBP, reflecting the environment and pharmacokinetics at the infection site.Methods: AF was obtained from nine cirrhotic patients with non-infected ascites. Growth of nine bacterial strains (three Escherichia coli, four Staphylococcus aureus, one Enterococcus faecalis, and one Klebsiella pneumoniae) in individual AF was assessed and correlated with biomarkers including potential risk factors for SBP. Ceftriaxone time-kill experiments, in which the pharmacokinetic profile observed in AF following a 1 g intravenous infusion was replicated, were performed with two E. coli and two S. aureus isolates with minimum inhibitory concentrations around the ceftriaxone resistance breakpoint.Results: Significant correlations were found between bacterial growth and AF levels of protein (Spearman's rank correlation coefficient ρ = −0.35), albumin (ρ = −0.31), and complement C3c (ρ = −0.28), and serum levels of bilirubin (ρ = 0.39) and aspartate aminotransferase (ρ = 0.25). Ceftriaxone was active in AF, even against resistant isolates, generally resulting in ≥2 log reductions in bacterial count within 24 h.Conclusion: Ascites patients may be predisposed to or protected against SBP based on the antimicrobial capacity of their AF. Ceftriaxone at clinical AF concentrations is active in the AF environment.